A systematic review and meta-analysis on the global status of Trichomonas vaginalis virus in Trichomonas vaginalis. (September 2021) - Bahadory, Saeed; Aminizadeh, Selva; Taghipour, Ali; Bokharaei-Salim, Farah; Khanaliha, Khadijeh; Razizadeh, Mohammad Hossein; Soleimani, Alireza; beikzadeh, Leila; Khatami, Alireza
Abstract: Background: The small (4.5–5kbp), double-stranded Trichomonas vaginalis virus (TVV) that inhabits in the T. vaginalis parasite has been potentially associated to parasite virulence or its drug resistance. The aim of present study was to estimate the global and regional status of TVV in T. vaginalis . Methods: A systematic search was conducted for published articles between January 1990 and December 2020 by using five major databases include PubMed, Embase, Scopus, and Web of Science as well as Google scholar search engine. The random-effect model was applied for pooled prevalence of TVV, geographical distribution, and heterogeneity by comprehensive meta-analysis (V2.2, Bio stat) software. Findings: A total of 28 studies were included for final meta-analysis. The pooled prevalence of TVV was estimated at 47% (95% CI, 39.3–54.8%). With respect to WHO regions, the lowest and highest prevalence rates were reported from South-East Asia 23% (95% CI, 12–41%) and African 66% (95% CI, 25–92%), respectively. Considering the countries, the prevalence was highest in the Brazil 90% (95% CI, 73–97%) and lowest in the South Korea 14% (95% CI, 4–35%). Conclusion: The high prevalence of the parasitic virus emphasizes the need to pay attention to the behavior of the parasite, both in terms of clinical symptoms and drug resistance. Moreover, it is suggested that more studies (i.e. in vitro, in vivo, and case-control studies) should be conducted for deep understanding of this coexistence. Highlights: The protozoan parasite Trichomonas vaginalis is highly prevalent and has been reported to be infected with a virus of the totaviridae family called T. vaginalis virus (TVV). Trichomonas vaginalis virus can possibly influence parasite behaviors; different types of the virus isolated from the parasite, the most common of which is TVV1. Estimating the prevalence of the virus in infected protozoa can be useful in investigating the behavior of the parasite. The present study is the first report on the prevalence of parasitic virus (TVV).